KEDUDUKAN WARIS ANAK ANGKAT MENURUT HUKUM WARIS ADAT BALI - Ketut Meta (Jurnal Cakrawala Hukum, 2017)
Children adoption already existed since a long time ago. However, the position of adopted children weredifferent from one region to another region in Indonesia. Bali people followed patrilineal kinship. It made theposition of a son hold a very important role. Therefore each family really wanted to have a son. For the familiesthat did not a have a son, they adopted a son. There were two kinds of adoption in Bali custom. They were: first,children adoption followed with tradition ceremony meperas or Widi Widana, witnessed by custom chief andpeople or society; second, children adoption which was not followed withtradition ceremony meperas or WidiWidana.The first adoption made the adopted son break the relation with his biological parents, and he cameinto his adopting fathers family. In the case of heir, he was not the heirs of his biological father but he was theheirs of his adopting father.